ANALISIS KETERAMPILAN MEMBACA KRITIS GEN-Z DALAM MENYIKAPI INFORMASI YANG BEREDAR DI MEDIA SOSIAL - Zhahira Adita Putri Jawawi; Yessar Rio Ardeva; Mohammad Rafa Hardyan Nugraha; Ajeng Putri Mujiono; Trinil Dwi Turistiani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze Generation Z’s reading skills and interest in reading when dealing with information circulating on social media. The study employs a descriptive qualitative approach, using data collection techniques in the form of interviews with five narasumberts from Generation Z who actively use social media as a daily source of information. The results show that most narasumberts have fairly good reading habits and rely on social media as their primary information source with high usage frequency. The majority of narasumberts recognize the importance of verifying information, although their ability to identify fake news varies among individuals. Some narasumberts still tend to assess the authenticity of information based on its presentation rather than by checking primary sources. Factors hindering reading interest include complex language, a lack of visual elements, and the prevalence of clickbait news. This study concludes that improving Generation Z’s reading literacy and digital literacy requires a collaborative approach involving individuals, educational institutions, the government, and digital platforms.